terrain : Ideas and Inspiration for Decorating the Home and Garden - Lehmkuhl, Greg; Lees, Caroline; Salazar, Isa (New York : Artisan, 2018)
Provides suggestions for container gardening, wreaths from natural materials, flower arrangements using wild items, and holiday decorations, and considers possibilities for each of the seasons as well as for Christmas time.
Includes index.
Keywords: Gardening -- Pictorial works; Interior decoration